LANGUAGE, THOUGHT, AND REALITY: LINGUISTIC RELATIVITY IN THE MODERN WORLD (SCIENCE TIME JOURNAL, 2026)
The relationship between language and thought has long been a central concern in linguistics and cognitive science. This study explores the concept of linguistic relativity and its relevance in the modern, globalized, and technology-driven world. Drawing on qualitative analysis and interdisciplinary perspectives, the article examines how language influences perception, categorization, and social interaction. Particular attention is given to multilingualism, cultural context, and the role of artificial intelligence in shaping language use. The findings suggest that while language does not strictly determine thought, it significantly guides cognitive processes and worldview construction. The study highlights the importance of linguistic awareness in fostering cross-cultural understanding and responsible technological development.